Interactive Mobile Learning-Based Gamification to Improve the Collaboration Skills of 11th Grade Students in High School - Sujarwo, Fakhrudin; Sariyatun; Rejekiningsih, Triana (Journal of Education Technology, 2023)
Instilling multiculturalism and a community attitude of cooperation in maintaining national integration can be done through the Sociology learning process. However, the Sociology learning process that occurred have not been carried out optimally. Thus, collaboration skills as an essential skill in building a 21st-century knowledge society need to be achieved. It can be seen interaction between students who still prioritize personal interests rather than group interests to attain common goals. This happened in the Sociology subject in class XI high school. Based on these problems, this research aimed at optimizing the Sociology learning process through the development and elaboration of gamification-based mobile learning media to improve collaboration skills. This research was a development research (R&D). The gamification-based mobile learning media was tested using a static group comparison design approach in the experimental class and comparison class. The test results were that the practical course scored 82.66, and the comparison class scored 67.40. It indicated that, there were an average difference where the experimental type was 15.26 points superior or 22.63% premium to the comparison class. The t-test results showed that gamification-based mobile learning media products improved collaboration skills. It was concluded that the mobile learning media developed is suitable for use and effective in enhancing the collaboration skills of class XI high school students.